Ecosystem Health Assessment and Driving Factor Analysis of Panjin Reach of Liaohe River Basin Based on PSR Model - YANG Heqing; HU Huiqin; ZHANG Qinxu; QIN Mengen; ZHANG Mingliang; HOU Jun (Renmin Zhujiang)
To evaluate the ecosystem health of Panjin reach in the Liaohe River Basin,based on the data collected from 2010 to 2020 in the study area,this paper adopts a pressure-state-response (PSR) evaluation model and selects 13 evaluation indicators.The entropy weight method is introduced to calculate the weight,and the fuzzy relation matrix method is adopted to calculate the membership degree.As a result,the comprehensive evaluation index (CEI) in the Panjin section of the Liaohe River is obtained,and then the ecosystem health of the study area is evaluated.The results show that the CEI indexes of this area from 2010 to 2020 are 0.343,0.341,0.279,0.425,0.418,and 0.464 respectively,and the overall ecosystem health changes from an “unhealthy” level to a “generally healthy” level.This study indicates that the total volume of water resources,policies and regulations,construction of protected areas,landscape diversity index,industrial wastewater discharge,and chemical oxygen demand in water have a great influence on the ecosystem health of the study area,with the weight values of 0.209 7,0.179 7,0.141 9,0.136 8,and 0.106 3 respectively.The overall weight of hydrologic and water environment factors involved in all the indicators is 0.620 7,with the effect degree more than half of all indicators.These hydrologic and water environment factors play a more direct role in this area.Therefore,the ecosystem health improvement in the study region requires management and remediation from the perspective of hydrology and the water environment.Thus,to improve the ecosystem health of the study area,it is necessary to carry out the management and regulation from the perspectives of hydrology and the water environment.